Employee Perceptions of Job Conditions in Explaining Employee Job Satisfaction: A Stakeholder’s Perspective (Tanzania Journal for Population studies and Development, 2014)
This study examines employee perceptions of job conditions in their workplaces in explaining an organisation’s employee-outcomes. It argues that when employees have positive perceptions of various workplace conditions, their attitudes influence their perceived job satisfaction. The study examines the extent to which employees consider important various employment conditions in the workplace and relate these attitudes towards their job satisfaction. It hypothesizes that employees’ perceptions of fairness in workplaces mediate the relationship between perceptions of job conditions and employees’ job satisfaction. Data for employee attitudinal measures was collected by soliciting employee surveys from five different centres of financial and higher education institutions in Tanzania. The study concludes that there is a positive relationship between positive employee perceptions towards employment conditions and perceived job satisfaction.